ANALISIS PENERAPAN GAP (GOOD AGRICULTURAL PRACTICE) DALAM PENGELOLAAN KEBUN KELAPA SAWIT PADA PT DUTA REKA MANDIRI DESA SUNGAI DUA KECAMATAN RAMBUTAN KABUPATEN BANYUASIN - Budi Fachrudin; Yuwinti Nearti; Rahmah Awaliah (Agripita: Jurnal Agribisnis dan Pembangunan Pertanian, 2020)
This research aimsto elaborate the implemnetation of GAP(Good Agricultural Practise) and to analyze the effects of GAPimplementation on cultivation technic, plantation management and harvesting of Palmoil Plantation Company Duta Reka Mandiri. The research used survey method to collecttime series data. Data were scored analyzed using multiple linear regressions. The results showed thatGAP implementation of Duta Reka Mandiri Company had been set to exelent level. In addition, GAPimplementation on plantation management, harvesting, participation of farmers and planting year significantly aff